Design of high scalability multi-subcarrier rof hybrid system based on optical CDMA/TDM - Ahmed Ghanim Wadday Ghanim Wadday; Faris Mohammed Ali; Hayder Jawad Mohammed Albattat (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The technology of radio over fiber (RoF) regard a crucial point to solve problems in wireless communication system. As well as, the growth of internet applications also reveals a tremendous increase in bandwidth for different applications. Therefore, the development of optical networks is very important that have maximum bandwidth by using different multiple access techniques. Optical code division multiple access (OCDMA) technique has considered as a good solution for high bandwidth network. Hybrid optical systems of OCDMA and time division multiplexing (OTDM) has been proposed in this paper to increase the number of simultaneous users. The results of hybrid OCDMA and OTDM system demonstrate that this system can make a considerable increase in the network scalability while ensuring sufficient data rate and an acceptable bit error rate. Where M-user OCDMA signals can be transmitted in different channels of an OTDM system. Due to its wide band facility compared with other access techniques, OCDMA used here. In addition to its high scalability for our radio network, the OTDM and SCM utilized. The combination of these efficient access technique and powerful time-sharing media are lead to increase the framework system scalability.